1997
DOI: 10.1163/156856297x00010
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition parameters of potential thermosensitive drug release systems based on polymers of N-alkylmethacrylamides

Abstract: The phase separation and its thermohysteresis in dilute aqueous solutions of polymeric components of potential drug release systems (homopolymers and copolymers of N-isopropylacrylamide, N-isopropylmethacrylamide, N-propylmethacrylamide, N-sec-butylmethacrylamide, and N-(2-hydroxypropyl)methacrylamide) was studied, both on heating and cooling. Plots of light transmittance vs temperature were constructed and the parameters characterizing them were correlated with polymer structures. Qualitative information was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…A more flexible control over the LCST value is achieved by using statistical copolymers. They can be either obtained by direct copolymerization of appropriate monomers in suitable amounts [12][13][14][15][16][17] or by partial chemical modification [18][19][20][21], and enable the fine-tuning of the LCST value. Yet, except for the rare case of ideal azeotropic copolymerizations (i.e., all copolymerization reactivity ratios are close to unity) [22][23][24][25][26][27], this gives rise to product mixtures that risk blurring the transition.…”
Section: Introductionmentioning
confidence: 99%
“…A more flexible control over the LCST value is achieved by using statistical copolymers. They can be either obtained by direct copolymerization of appropriate monomers in suitable amounts [12][13][14][15][16][17] or by partial chemical modification [18][19][20][21], and enable the fine-tuning of the LCST value. Yet, except for the rare case of ideal azeotropic copolymerizations (i.e., all copolymerization reactivity ratios are close to unity) [22][23][24][25][26][27], this gives rise to product mixtures that risk blurring the transition.…”
Section: Introductionmentioning
confidence: 99%
“…Their thermosensitivity makes these systems in general interesting for possible biomedical and technological applications, e.g. as drug release systems [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Although polyalkylacrylamides and polyalkylmethacrylamides 27 exhibit a broad spectrum of LCSTs, most studies largely covered the case of poly(NIPAM). Few works were devoted to other derivatives, such as, for instance, poly(N-isopropylmethacrylamide) (NIPMAM) displaying a LCST between 38 to 44°C as reported by several authors; 28 -30 in addition, a hysterisis phenomenon of the transition was also observed 31,32 when cooling back the polymer solution below the LCST. One alternative pathway to prepare polymers with LCST values different from that of poly(NIPAM), consists of performing the copolymerization of NIPAM with monomers having hydrophobic or hydrophilic character, [33][34][35][36][37] and such a method was also successfully applied in the case of poly(NIPAM)-based latexes.…”
Section: Introductionmentioning
confidence: 99%